2002
DOI: 10.1103/physrevlett.89.127401
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Carrier-Envelope Offset Phase of Few-Cycle Pulses in Nonperturbative Resonant Nonlinear Optics

Abstract: We study the influence of the carrier-envelope offset phase of few-cycle pulses on nonperturbative resonant extreme nonlinear optics in a semiconductor. If the Rabi frequency becomes comparable to the light frequency, the different Rabi sidebands interfere around twice the laser center frequency, giving rise to a signal which strongly depends on the carrier-envelope offset phase. This signature should be measurable in GaAs samples. DOI: 10.1103/PhysRevLett.89.127401 PACS numbers: 78.47.+p, 42.50.Md, 42.65.Re … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 20 publications
5
53
0
Order By: Relevance
“…For each slice, this approach offers a simple analytical formula for the ratio of level population amplitudes, resulting in equally simple analytical formulae for population inversion, induced dipole moment, and spectrum of the radiation emitted by this dipole. A good quality of the method is proved by showing that the resulting photon-emission spectra reproduce the numerically calculated ones available in literature [8,9,[13][14][15][16][17][18][19]. Moreover, the method indicates weak points of the square--wave solution of Tritschler et al [23] and is shown to be particularly useful in the area of extreme nonlinear optics [23], i.e., when few-cycle, strong pulses stimulate significant population dynamics in a two-level system on a timescale of half the optical cycle.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…For each slice, this approach offers a simple analytical formula for the ratio of level population amplitudes, resulting in equally simple analytical formulae for population inversion, induced dipole moment, and spectrum of the radiation emitted by this dipole. A good quality of the method is proved by showing that the resulting photon-emission spectra reproduce the numerically calculated ones available in literature [8,9,[13][14][15][16][17][18][19]. Moreover, the method indicates weak points of the square--wave solution of Tritschler et al [23] and is shown to be particularly useful in the area of extreme nonlinear optics [23], i.e., when few-cycle, strong pulses stimulate significant population dynamics in a two-level system on a timescale of half the optical cycle.…”
Section: Introductionmentioning
confidence: 87%
“…The latter is known [8,9,12,[24][25][26][27] to be a relevant quantity determining the response of the system in the regime of few-cycle pulses. Traditionally, there has been solved in different coupling regimes either a set of two linear differential equations for b k with no RWA applied (e.g.…”
Section: The Analytical Solution For Short Time Intervals and Iteratimentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the period of these CEP-dependent signals is 2π . This is different from the interference case in symmetric media [15,20,21], in which the CEP-dependent period is π . To illustrate the underlying physics, we calculate the dipole-induced emitted field spectra (Ê em (ω) ∝ FFT − ∂P x ∂t [44]) from the medium at the same propagation distance as in figure 1.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Previous investigations in inversion-symmetric media have shown that these CEPdependent signals are originated from the interference effects between different harmonic components. The CEP-dependent period in inversion-symmetric media is π , which means that the sign of the electric field cannot be determined in these phenomena [15,20,21].…”
Section: Introductionmentioning
confidence: 99%